A MODERN SOLUTION THAT HAS A POSITIVE IMPACT ON LOGISTICS SERVICES AND SIGNIFICANTLY REDUCES INTERSECTION FATALITIES: A MODERN SOLUTION THAT HAS A POSITIVE IMPACT ON LOGISTICS SERVICES AND SIGNIFICANTLY REDUCES INTERSECTION FATALITIES - Ruzmatovich, Tajimuratov Umid; Kayumovich, Adilov Shukhrat; Ruzmat Otajanovich, Tajimuratov; Abdusami, Tajimuratov; Ugli, Umid (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Year after year, the problems on the world's roads are getting worse. According to the UN Economic Commission for Europe (ECE) 2006 Report on the 1968 Geneva Convention "Road Signs and Signals", the rules are periodically updated to take into account the growing demands for human safety, environmental protection, and the rapid development of technological progress around the world (Report IEC UN, New York and Geneva, 2007). Unfortunately, for about a hundred years now, no drastic measures have been taken against the causes of road traffic accidents around the world. Our research is focused on reducing intersection congestion, traffic accidents, and related deaths. A new road sign and traffic light were invented. According to the conclusions of domestic and foreign scientists, the invented sign and traffic light should be a great success in practice.